2020
DOI: 10.1101/2020.11.01.364349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate warming weakens local adaptation

Abstract: Anthropogenic climate change is generating mismatches between the environmental conditions that populations historically experienced and those in which they reside. Understanding how climate change affects population performance is a critical scientific challenge. We combine a quantitative synthesis of field transplant experiments with a novel statistical approach based in evolutionary theory to quantify the effects of temperature and precipitation variability on population performance. We find that species' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 52 publications
5
28
0
Order By: Relevance
“…2020) and to temporal variation in climate conditions (Bontrager et al. 2020). We searched for studies through March 19, 2017, which moved at least one population to multiple locations or multiple populations to at least one location and subsequently measured at least one component of fitness (see next).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2020) and to temporal variation in climate conditions (Bontrager et al. 2020). We searched for studies through March 19, 2017, which moved at least one population to multiple locations or multiple populations to at least one location and subsequently measured at least one component of fitness (see next).…”
Section: Methodsmentioning
confidence: 99%
“…For models of local adaptation, we also included the temperature deviation between a site's historical conditions and those during the experiment, which could alter the strength of local advantage (calculation methods are described in Bontrager et al. 2020).…”
Section: Methodsmentioning
confidence: 99%
“…We used a database of studies that had conducted transplant experiments moving populations of terrestrial species at geographic scales, which was previously compiled to examine adaptation to biotic interactions (Hargreaves et al, 2020) and to temporal variation in climate conditions (Bontrager et al, 2020). We searched for studies through 19 March 2017 that moved at least one population to multiple locations or multiple populations to at least one location and subsequently measured at least one component of fitness (see below).…”
Section: Methodsmentioning
confidence: 99%
“…To account for this, we calculated the geographic distance, absolute temperature difference, and absolute precipitation difference between each source and site. For models of local adaptation, we also included the temperature deviation between a site’s historical conditions and those during the experiment, which could alter the strength of local advantage (calculation methods are described in Bontrager et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…We set 6 = 196 so that there was a 40% fitness difference between individuals perfectly adapted to the two extremes of the distribution of phenotypic optima. This was motivated by empirical studies of local adaptation that have demonstrated such fitness differences in numerous species (Hereford 2009;Bontrager et al 2020); see Appendix.…”
Section: Simulating Local Adaptationmentioning
confidence: 99%